2013
DOI: 10.7314/apjcp.2013.14.3.1957
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Awareness and its Determinants among a Selected Malaysian Population

Abstract: Objective: To assess oral cancer awareness, its associated factors and related sources of information among a selected group of Malaysians. Methods: A cross-sectional survey was conducted on all Malaysian ethnic groups aged ≥15 years old at eight strategically chosen shopping malls within a two week time period. Data were analysed using chi-square tests and multiple logistic regression. Significance level was set at α <0.05. Results: Most (84.2%) respondents had heard of oral cancer. Smoking was the most (92.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
54
6
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 29 publications
25
54
6
6
Order By: Relevance
“…These results support previous findings, which report that mass media is a common source of information regarding oral cancer (Peker and Al-Kurt 2010;Park et al, 2011;Ghani et al, 2013;Tadbir et al, 2013). A recent Malaysian study has assessed the impact of promoting oral cancer awareness of the public using a mass media campaign; the results showed a significant increase in the public awareness regarding general knowledge and etiology factors of the disease (Saleh et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…These results support previous findings, which report that mass media is a common source of information regarding oral cancer (Peker and Al-Kurt 2010;Park et al, 2011;Ghani et al, 2013;Tadbir et al, 2013). A recent Malaysian study has assessed the impact of promoting oral cancer awareness of the public using a mass media campaign; the results showed a significant increase in the public awareness regarding general knowledge and etiology factors of the disease (Saleh et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Our study population also showed an inadequate knowledge regarding risk factors. Although more than two thirds of the participants identified tobacco use (smoking and smokeless tobacco use) as the main risk factors, similar to earlier studies conducted in Australia, England, India, Iran, Malaysia and the USA (Horowitz et al, 1995;Warnakulasuriya et al, 1999;Tadbir et al, 2013;Park et al, 2011;Agrawal et al, 2012;Ghani et al, 2013), only small proportion of participants were aware that old age, alcohol consumption, and sun exposure in the case of lip cancer are also potential risk factors. The greater awareness of tobacco as a risk factor could be attributed to anti-tobacco media campaigns explaining the adverse effects of smoking.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Some factors are modifiable and the detrimental repercussions of this dreadful disease can be prevented if the population is made aware of the causative risk factors, various available prevention strategies and existing early detection modalities through community programs (Ghani et al, 2013). Like in most of the developing parts of the world, Saudi Arabia also faces scarcity in organized cancer intervention or early detection screening programs.…”
Section: Discussionmentioning
confidence: 99%